Analysis design and experimental verification of a two-switch forward converter - Wuti, V.; Bunlaksananusorn, C. (My University, 2015)
A forward converter is an isolated DC-DC converter widely used in switching power supplies with output power ratings ranging from 50W to 400W. The conventional forward converter requires a transformer with a tertiary winding to assist in magnetic core reset and subjects its power switch to a high voltage at turn-off. These shortcomings are eliminated in the two-switch forward converter. This paper presents analysis, design and experimental verification of a two-switch forward converter. First, the converter operation is analyzed, enabling its key equations and important waveforms to be established. Then, the converter design, including both the power circuit and feedback controller, is illustrated in detail. Finally, experimental results from the prototype circuit are presented to confirm the validity of the analysis and design.
Keywords: Analysis; Control; Design; Two-switch forward converter